Systemic Amyloidosis Presented with Persistent Cough: A Case Report and Review of Literature - Sayeed, Md Abu; Sattar, Md Abdus; Paul, Sujat; Siraji, Dilruba; Das, Uzzwal Kanti (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: systemic amyloidosis; immunoglobulin light chain-derived amyloidosis (AL); respiratory amyloidosis; coughs DOI: 10.3329/jcmcta.v21i1.7683 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):70-73